The The Construction of Guru Bakhiet's Gender Interpretation: Between Subordination and Women's Empowerment - Arabi, Ibnu; Mujahid, Ahmad (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study aims to examine the construction of Guru Bakhiet's gender interpretation in his interpretation of a number of verses of the Qur'an, focusing on the theme of subordination and women's empowerment. Guru Bakhiet interprets Qur'anic verses related to women, such as Surah al-Baqarah [2]: 228, Surah an-Nisa [4]: 1 and 34, Surah al-An'am [6]: 137, and Surah al-Isra [17]: 1, with an approach that prioritizes justice, equality, and protection of women's rights. This research uses critical analysis methods and hermeneutic approaches, this research reveals how Guru Bakhiet interprets verses related to women, including the obligation to wear the hijab, the position of husband and wife, women's rights, and women's relationships with men in the context of marriage. The results of the study show that Guru Bakhiet's interpretation is influenced by the dynamics in gender understanding in his interpretation, which not only reflects local traditions and culture, but also shows the potential to formulate a more inclusive view and empower women within the framework of Islamic teachings. Guru Bakhiet's interpretation shows that there is a tendency to put women in a subordinate position and at the same time try to empower women through fair religious learning, as well as the affirmation of women's rights in the family. Although she emphasizes the obligation of women to maintain honor and maintain manners, the interpretation also includes aspects that support the education and protection of women, such as in her views on the treatment of girls and efforts to prevent injustice in husband-wife relationships. So, this interpretation emphasizes the importance of women's empowerment through education and fair treatment, as well as criticizing practices that have the potential to suppress the role of women in society. Thus, it can be concluded that Guru Bakhiet's tafsir combines aspects of subordination and empowerment, by fighting for women's rights within the framework of humanist and contextual Islamic teachings.